Computer code for double beta decay QRPA based calculations - Barbero, C. A. [UNESP] (2014)
The computer code developed by our group some years ago for the evaluation of nuclear matrix elements, within the QRPA and PQRPA nuclear structure models, involved in neutrino-nucleus reactions, muon capture and beta(+/-) processes, is extended to include also the nuclear double beta decay.